Construction and sustained release of konjac glucomannan/naringin composite gel spheres - Dao, Liping; Chen, Siyang; Sun, Xiangyun; Pang, Wenyuan; Zhang, Hengzhe; Liao, Jun; Yan, Jiqiang; Pang, Jie (Frontiers in Nutrition, 2023)
Objective To improve the bioavailability of active substances and reduce the toxic and side effects on the human body, natural biological macromolecules are used to load active substances and control their release speed in different environments of the human body. In this study, mesoporous silica (MSN) was combined with konjac glucomannan (KGM) and sodium alginate (AC) to prepare pH-sensitive konjac glucomannan/sodium alginate–mesoporous silica loaded naringin gel spheres (KS/MSN). On this basis, the structure, morphology, and release properties of the composite gel spheres were characterized. The results showed that the cumulative release rates of both simulated gastric fluid (SGF) and Simulated colonic fluid (SCF) were lower than that of simulated small intestinal fluid (SIF), which indicated that the prepared composite gel spheres were pH-sensitive to SIF and obtained the best release rate of about 70% under SIF environment. Methods The pH-sensitive konjac glucomannan/sodium alginate composite gel spheres (KGM/SA) were prepared by combining inorganic nano-materials mesoporous silica (MSN) with natural macromolecular polysaccharides konjac glucomannan (KGM) and sodium alginate (SA) and characterized. Results The results showed that there was a process of ionic crosslinking and entanglement between konjac glucomannan (KGM) and sodium alginate (SA). Naringin (NG) and mesoporous silica (MSN) were successfully compounded and had good compatibility. The gel microstructure diagram showed that the addition of MSN improved the gel properties of KGM, and KGM and SA gel spheres (KGM/SA) had good compatibility with mesoporous silica/naringenin nanoparticles (NG/MSN). The study of the simulated digestive environment of the gastrointestinal release medium showed that Konjac glucomannan/sodium alginate-mesoporous silica loaded naringin gel spheres (KS/NM) composite gel spheres had the best slow-release effect and the highest final-release completion degree in SIF. The release of NG from KS/NM composite gel spheres showed a slow upward trend. The results showed that KS/NM composite gel spheres were pH-sensitive. Conclusion The KS/NM composite gel spheres showed obvious pH sensitivity to the release of NG, and the gel spheres had a good sustained release effect on NG.